ESTUDO DE UMA PACIENTE QUE SOFRE UMA MORDEDURA DE COBRA - Rosane, Cleci P.; Kolankiewicz, Adriane C. B.; Silveira, Caroline D. O.; Menin, Gisele E.; Dallabrida, Francieli A.; Rorato, Luciéle (Salão do Conhecimento, 2013)
Resumo